Academic extension as a tool of educational practice in the process of training nurses (Research, Society and Development, 2021)
Objective: to discuss the importance of university extension in the process of training the nursing professional, based on an experience report of students from a baccalaureate nursing course. It consists of a descriptive study of qualitative approach of the experience report type, built by means of a critical-reflexive analysis, through the experiences lived on the activities developed by the Education in Health Extension Project (PROES) of a private university center in Maceió, Alagoas. The activities developed by the project were based on lectures, conversation circles, and playful meetings about issues involving health promotion for children, adolescents, and adults, being held during the year 2019 to 2020, once a month, having as field of action a health unit and two schools. It is observed the importance of university extension in the nursing education process, given that the contributions of extra-academic practice bring benefits not only for the community, but also for nursing students, as presented in this report, especially the interaction between research-teaching-extension, theory-practice relationship, production of learning, acquisition of skills and competencies, autonomy, formulation of critical and reflective thinking to solve real situations/problems. In short, it is evident the relevance of extension activities during graduation since this process favors the development and strengthening of educational practices, of investigative reasoning and the dissemination of knowledge associated with the reality experienced, as well as the stimulation for research based on scientific evidence, contributing to the construction of a professional, ethical and humanized attitude towards the chosen area.